Effectiveness of Personalized Learning Model Using Digital Flipbooks with Sidoarjo Local Wisdom to Improve Multiliteracy of Elementary School Students in the Digital Era - Istiq'faroh, Nurul; Hendratno, Hendratno; Veruna Enun Kharisma, Nanda; Susetyo Rukmi, Asri; Rusanti, Mita; Aini, Nurul; Hadi Wibowo, Amiruddin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to examine the effectiveness of personalized learning model using digital flipbooks with Sidoarjo local wisdom in improving multiliteracy of elementary school students. Method: This study used quantitative with a one-group pretest-posttest design. The sample was 27 students from grade five at SDN Kedungsolo, Porong District, Sidoarjo Regency. The instruments used were a cultural literacy test and a reading interest questionnaire. Data were analyzed with two techniques: normality test and hypothesis test using SPSS for cultural literacy, and outer loading, validity, and reliability analysis for the questionnaire using SmartPLS. Results: The results showed that the average score of students increased significantly, from 54.07 in the pretest to 87.78 in the posttest, with Sig. (2-tailed) value < 0.05. The questionnaire also showed higher reading interest and awareness after using the digital flipbook, meaning that digital flipbooks combined with personalized learning are effective to improve students’ multiliteracy, both in cultural literacy and reading interest. Novelty: In conclusion, learning innovation with technology that integrates local wisdom can be a good solution to improve the quality of education in the 21st century, while also keeping the value of local culture. This study uniquely integrates a Personalized Learning Model with digital flipbooks featuring Sidoarjo local wisdom to enhance students’ multiliteracy, offering a contextual and innovative approach for 21st-century elementary education.